Forecasted stability of Mediterranean evergreen species considering global changes (GLOBAL CHANGE AND PROTECTED AREAS, 2001)
Plant communities of the Mediterranean climate Regions are exposed to high temperatures, high radiation and water stress during summer, they are dominated by evergreen sclerophyllous species and drought semi deciduous species. To define the adaptive strategies, anatomical and morphological leaf traits of Quercus ilex L., Phillyrea latifolia L. (typical evergreen sclerophyllous species) and Cistus incanus L., (a drought semi deciduous species), growing in the Mediterranean maquis along Pome's coast line (Italy) were analysed. The typical evergreen sclerophyllous species have long leaf life span (from 1 to 4 years), steeper leaf inclination (average 56 degrees), higher specific leaf mass (average 21.3 mg cm(-2)) and the highest leaf thickness (average 324 mum). The semi deciduous species have a lower leaf life span (from 4 to 8 months), a lower leaf inclination (44 degrees +/- 13 degrees), a lower specific leaf mass (14.7 +/-1.5 mg cm(-2)) and a lower leaf thickness (244 +/- 15 mum). The more xeromorphyc species (Q. ilex and P. latifolia) may be at a competitive advantage considering the forecasted air temperature increase in the Mediterranean basin. Increasing drought stress may in fact determine a shortening of leaf life span that may prove to be critical for C. incanus. Knowledge of plant response to stress factors is important in the perspective of climatic changes.
Meeting on Global Change and Protected Areas, LAQUILA, ITALY, SEP, 1999

Leaf anatomy, inclination, and gas exchange relationships in evergreen sclerophyllous and drought semideciduous shrub species (PHOTOSYNTHETICA, 1999)
There are significant differences in leaf life-span among evergreen sclerophyllous species and drought semideciduous species growing in the Mediterranean maquis. Cistus incanus, which has a leaf life-span of four-eight months, was characterised by the highest net photosynthetic rates (PN). while Quercus ilex and Phillyrea latifolia, which maintain their leaves two-three and two-four years, respectively, had a lower PN- The longer leaf life-span of the two evergreen sclerophyllous species may be justified to cover the high production costs of leaf protective structures such as cuticle, hairs, and sclereids: cuticle and hairs screen radiation penetrating into the more sensitive tissues, and sclereids have a light-guiding function. Q. ilex and P. latifolia have the highest leaf mass/area ratio (LMA = 209 g m(-2)) and a mesophyll leaf density (2065 cells per mm(2) of leaf cross section area) about two times higher than C. incanus. In the typical evergreen sclerophyllous species the steepest leaf inclination (alpha = 56 degrees) reduces 42% of radiation absorption, resulting in a reduced physiological stress at leaf level, particularly in summer. C. incanus, because of its low leaf life-span, requires a lower leaf investment in leaf protective structures. It exhibits a drastic reduction of winter leaves just before summer drought, replacing them with smaller folded leaves. The lower leaf inclination (alpha = 44 degrees) and the lower LMA (119 g m(-2)) of C. incanus complement photosynthetic performance. Water use efficiency (WUE) showed the same trend in Q. ilex, P. latifolia, and C. incanus, decreasing 60% from spring to summer, due to the combined effects of decreased CO2 uptake and increased transpirational water loss.